DEVELOPMENT AND VALIDATION OF A HPLC METHOD FOR THE SIMULTANEOUS DETERMINATION OF PSEUDOEPHEDRINE, DEXTROMETHORPHAN, AND TRIPROLIDINE IN THEIR COMBINED COUGH AND COLD SYRUPS - Abu Reid, Imad Osman; Gad Kariem, Elrasheed Ahmed (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
A simple and efficient liquid chromatographic method has been developed and validated for the simultaneous determination of pseudoephedrine, dextromethorphan, and triprolidine in cough and cold syrup. The separation of the analytes was achieved within 10min, employing a mixture of 50% v/v methanol-water containing 35.07 mM/L ammonium acetate adjusted to pH 5.58 as isocratic mobile phase, pumped at 1.0 ml min-1 through a strong cation exchange column (10Âµm particle size). The analytes were detected at 265nm. Statistical experimental designs and graphic representations (response surface methodologies, Pareto charts) were used for optimizing the mobile phase composition. The linearity of the calibration (r>0.99, n =18) in the relevant ranges (up to 125% of the expected concentrations of the analytes in the formulation), method accuracy (RSD <2.0%), repeatability (RSD<2.0%) and intermediate precision, were verified. System suitability parameters were also determined. The validated method was successfully employed for the routine analysis of a syrup pharmaceutical preparation against cough and cold, showing satisfactory analytes recoveries and precsion.